Validation of long‐term measurements of water vapor from the midstratosphere to the mesosphere at two Network for the Detection of Atmospheric Composition Change sites. Issue 2 (18th January 2013) - Nedoluha, Gerald E.; Gomez, R. Michael; Neal, Helen; Lambert, Alyn; Hurst, Dale; Boone, Chris; Stiller, Gabriele
Abstract : We present measurements from the Water Vapor Millimeter‐wave Spectrometer (WVMS) instruments at Table Mountain, California (34.4°N, 242.3°E), and Mauna Loa, Hawaii (19.5°N, 204.4°E), and highlight the extended altitude range of the measurements at these sites, which now provide measurements down to 26 km. We show that this extended altitude range has been acquired without disturbing the existing long‐term WVMS data set at Mauna Loa. Validation of the successful transition is provided by comparing WVMS measurements with coincident satellite measurements from the Aura Microwave Limb Sounder (MLS), the Atmospheric Chemistry Experiment, and the Michelson Interferometer for Passive Atmospheric Sounding. At the lowest altitudes where WVMS measurements are possible, we also compare with frost‐point hygrometer balloon measurements. The water vapor mixing ratios measured at 50 km over Mauna Loa are the highest ever reported in the WVMS (since 1996) or MLS (since 2004) time series. Particularly encouraging for the new 26 km WVMS measurements is that they indicate an increase between 2010 and 2011 that is comparable to that observed by other instruments. This shows that these measurements are sensitive to variations at this altitude and that the instrumental baseline remains stable. Key Points: WVMS instruments now provide water vapor measurements down to 26km This upgrade has not disturbed the long‐term mesospheric time series NH mid‐latitude stratospheric H2O increased between 2010 and 2011